System safety engineering and risk assessment : a practical approach - Bahr, Nicholas J. (CRC Press, Taylor & Francis Group, 2015)
"We all know that safety should be an integral part of the systems that we build and operate. The public demands that they are protected from accidents, yet the two constituencies--industry and government--don't always know how to reach this common goal"-- Resumé vydavatele
Keywords: bezpečnostní management; bezpečnost technických zařízení; bezpečnostní inženýrství; spolehlivost (technika); riziko; rizikový management; systémové inženýrství; safety management; safety of technical equipment; safety engineering; reliability (engineering); risk; risk management; systems engineering; monografie; monographs